DESAIN DAN SIMULASI HEATPIPE WITH SINK MENGGUNAKAN CFD DALAM PROSES KINERJA THERMAL NATURAL COOLING PADA KERETA API : DESIGN AND SIMULATION OF HEATPIPES WITH SINKS USING CFD IN THE PROCESS OF THERMAL NATURAL COOLING PERFORMANCE ON TRAINS - Fani Mifiantika (Program Studi Teknik Mesin PSDKU Polinema Kediri, 2024)
Natural cooling analysis with heat pipes is very important in cooling systems in rectifier components because their effectiveness can be influenced by a number of factors that need to be considered in their design and implementation. Here are some reasons why analysis is necessary. The design of thermal systems that use natural cooling with heat pipes must be analyzed to ensure that the heat pipes can handle the heat load generated by electronic components or other devices. This involves consideration of the size, shape, and heat distribution of heat pipes. The effectiveness of natural cooling can be affected by the operational environment in which heat pipes are used. Variables such as ambient temperature, humidity, and atmospheric pressure can affect the performance of heat pipes. This analysis helps adjust the design to match anticipated operational conditions.